SH2 Domain–Containing Phosphatase 2 Inhibition Attenuates Osteoarthritis by Maintaining Homeostasis of Cartilage Metabolism via the Docking Protein 1/Uridine Phosphorylase 1/Uridine Cascade. Issue 3 (2nd February 2022) - Liu, Qianqian; Zhai, Linhui; Han, Mingrui; Shi, Dongquan; Sun, Ziying; Peng, Shuang; Wang, Meijing; Zhang, Chenyang; Gao, Jian; Yan, Wenjin; Jiang, Qing; Chen, Dijun; et al.
Abstract : Objective: Protein tyrosine kinases regulate osteoarthritis (OA) progression by activating a series of signal transduction pathways. However, the roles of protein tyrosine phosphatases (PTPs) in OA remain obscure. This study was undertaken to identify specific PTPs involved in OA and investigate their underlying mechanisms. Methods: The expression of 107 PTP genes in human OA cartilage was analyzed based on a single‐cell sequencing data set. The enzyme activity of the PTP SH2 domain–containing phosphatase 2 (SHP‐2) was detected in primary chondrocytes after interleukin‐1β (IL‐1β) treatment and in human OA cartilage. Mice subjected to destabilization of the medial meniscus (DMM) and IL‐1β–stimulated mouse primary chondrocytes were treated with an SHP‐2 inhibitor or celecoxib (a drug used for the clinical treatment of OA). The function of SHP‐2 in OA pathogenesis was further verified in Aggrecan‐Cre ERT ; SHP2 flox/flox mice. The downstream protein expression profile and dephosphorylated substrate of SHP‐2 were examined by tandem mass tag labeling–based global proteomic analysis and stable isotope labeling with amino acids in cell culture–labeled tyrosine phosphoproteomic analysis, respectively. Results: SHP‐2 enzyme activity significantly increased in human OA samples with serious articular cartilage injury and in IL‐1β–stimulated mouse chondrocytes. Pharmacologic inhibition or genetic deletion of SHP‐2 ameliorated OA progression. SHP‐2 inhibitors dramatically reduced the expression of cartilage degradation–related genes and simultaneously promoted the expression of cartilage synthesis–related genes. Mechanistically, SHP‐2 inhibition suppressed the dephosphorylation of docking protein 1 and subsequently reduced the expression of uridine phosphorylase 1 and increased the uridine level, thereby contributing to the homeostasis of cartilage metabolism. Conclusion: SHP‐2 is a novel accelerator of the imbalance in cartilage homeostasis. Specific inhibition of SHP‐2 may ameliorate OA by maintaining the anabolic–catabolic balance.